Computed Tomography-Guided Preoperative Radiotracer Localization of Nonpalpable Lung Nodules - Bellomi, Massimo; Veronesi, Giulia; Trifirò, Giuseppe; Brambilla, Sarah; Bonello, Luke; Preda, Lorenzo; Casiraghi, Monica; Borri, Alessandro; Paganelli, Giovanni; Spaggiari, Lorenzo (The Annals of thoracic surgery, 2010)
We describe preoperative computed tomography (CT)–guided injection of radiotracer technetium 99m macroaggregates ( 99mTc-MAA) in challenging small lung nodules, intraoperative localization, and resection. Between November 2007 and February 2010, 44 patients with 47 lung nodules which were detected incidentally or at screening and that were 18F-fluorodeoxyglucose positron emission tomography ( 18F FDG-PET) positive or increasing in size at subsequent CT scans were candidates for surgical biopsy. Inclusion criteria for preoperative percutaneous CT-guided (low-dose technique) 99mTc-MAA localization included having at least one of the following characteristics: nodule size less than 1 cm, subsolid morphology, or distance from the pleura greater than 1 cm. Mean nodule size was 11 mm (range, 5 to 24 mm); 24 nodules were nonsolid, 15 nodules were partially solid, and 8 nodules had a solid morphology. Mean distance from the pleura was 11 mm (range, 0 to 35 mm). Localization complications included 13 minor asymptomatic pneumothoraces, 9 parenchymal hemorrhage suffusions, 1 mild allergic reaction to contrast medium, and 2 patients with chest pain after the procedure. Nine patients had mild extravasation of radiotracer into the pleura. In 2 cases, there was an extravasation of a significant quantity of radiotracer into the pleural cavity. Thoracoscopic biopsy was performed in 30 cases, 2 cases were converted to thoracotomy, and 12 patients underwent intentional thoracotomy. Asymptomatic subjects with suspicious nodules detected by screening or incidental CT are best candidates due to small lesion size and high percentage of nonsolid morphology, making thoracoscopic biopsy potentially difficult. Radiotracer localization is a safe, versatile, simple technique to help perform diagnosis with a minimally invasive approach in nonpalpable lung lesions.